Media Visualisasi Auditori Kinestetik (Vak) Terpadu Untuk Stimulasi Keaksaraan Awal Anak - Nunuk Trisukma Aceh; Putu Aditya Antara; Dewa Gede Firstia Wirabrata (Jurnal Bimbingan dan Konseling Indonesia, 2022)
This study aims to develsop an Integrated Kinesthetic Auditory Visualization (VAK) media for early literacy stimulation of children in Kamila Kindergarten, Kajanan Village, Buleleng District. In this study, the MDLC (Multimedia Development Life Circle) model is used. The subjects in this study used two media experts. The data collection in this study used a questionnaire method which was then analyzed using data analysis, namely quantitative data and qualitative data. The Integrated Kinesthetic Auditory Visualization Media (VAK) was declared valid with very good qualifications from the experts with the percentage of learning media expert validity results obtained a score of 95%. From these results, it can be concluded that the development of Integrated Kinesthetic Auditory Visualization (VAK) media for early literacy stimulation of children in Kamila Kindergarten has very high validity so that Integrated Kinesthetic Auditory Visualization (VAK) media for early literacy stimulation of children in Kamila Kindergarten is feasible to use. Abstrak: Penelitian ini bertujuan untuk mengembangkan media Visualisasi Auditori Kinestetik (VAK) Terpadu untuk stimulasi keaksaraan awal anak di TK Kamila, Kampung Kajanan Kecamatan Buleleng. Dalam penelitian ini menggunkan Model MDLC (Multimedia Development Life Circle). Subjek dalam penelitian ini menggunakan dua orang ahli media. Pengumpulan data dalam penelitian ini menggunkan metode angket yang kemudian dianalisis menggunkan analisis data yaitu data kuantitatif dan data kualitataif. Media Visualisasi Auditori Kinestetik (VAK) Terpadu dinyatakan valid dengan kualifikasi sangat baik dari para ahli dengan persentase hasil validitas ahli media pembelajaran diperoleh skor 95%. Dari hasil tersebut dapat disimpulkan bahwa pengembangan media Visualisasi Auditori Kinestetik (VAK) Terpadu untuk stimulasi keaksaraan awal anak di TK Kamila mendapatkan validitas sangat tinggi sehingga media Visualisasi Auditori Kinestetik (VAK) Terpadu untuk stimulasi keaksaraan awal anak di TK Kamila layak digunakan.